2015
DOI: 10.1021/acs.langmuir.5b01979
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Organization and siRNA Binding of Hyaluronic Acid-Coated Lipoplexes for Targeted Delivery to the CD44 Receptor

Abstract: Original Citation:Supramolecular organization and siRNA binding of hyaluronic acid-coated lipoplexes for targeted delivery to the CD44 receptor. Published version:DOI:10.1021/acs.langmuir.5b01979 Terms of use:Open Access (Article begins on next page) Anyone can freely access the full text of works made available as "Open Access". Works made available under a Creative Commons license can be used according to the terms and conditions of said license. Use of all other works requires consent of the right holder (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 58 publications
2
26
0
2
Order By: Relevance
“…We also observed that the HA and CD44 could specifically bind together. 27,28 The results suggest that the mechanism underlying the targeted therapy by siRNA might involve the reduced expression of CD44 in the ectopic endometria.…”
mentioning
confidence: 96%
“…We also observed that the HA and CD44 could specifically bind together. 27,28 The results suggest that the mechanism underlying the targeted therapy by siRNA might involve the reduced expression of CD44 in the ectopic endometria.…”
mentioning
confidence: 96%
“…The active targeting strategy was twofold. HA was used to target CD44 receptors overexpressed on the cellular surface of a variety of tumor carcinomas [85,86]. Additionally, GA-conjugated polymer drug delivery systems have recently been shown to actively target the liver to halt the progression of hepatic tumors [8789].…”
Section: Innovative Delivery Packagesmentioning
confidence: 99%
“…HA can also be conjugated to lipids ( Figure 3B) or polymers (Figure 5B) using chemical linkers [36][37][38][39][40][41]. HA-DOPE conjugate can be obtained through the creation of an amide bond between the carboxylic groups of HA and the amino group of DOPE [37].…”
Section: Polyplexes and Lipoplexes Modifi Ed With Hyaluronic Acidmentioning
confidence: 99%
“…HA-DOPE conjugate can be obtained through the creation of an amide bond between the carboxylic groups of HA and the amino group of DOPE [37]. Inclusion of HA-DOPE conjugates into cationic liposomes composed of [2-(2,3-didodecyloxypropyl) hydroxyethyl] ammonium bromide (DC) and DOPE ( Figure 3B) could improve transfection into tumor cells expressing the CD44 receptor [36][37][38][39]. Furthermore, DOTAP/DOPE liposomes modi ied with HA-DOPE conjugate ( Figure 3B) also exhibited improved stability in cell culture medium and a reduced cytotoxicity [40].…”
Section: Polyplexes and Lipoplexes Modifi Ed With Hyaluronic Acidmentioning
confidence: 99%